Marvel-verse: captain marvel ebook - DeConnick, Kelly Sue (Marvel-Verse., 2021)
Collects Avenging Spider-Man (2011) #9-10, Captain Marvel (2014) #7-8, Generations: Captain Marvel and Captain Mar-Vell (2017) #1. Carol Danvers flies higher, further, faster than anyone in the Marvel-Verse — and these are the stories that prove it! First, the world's greatest super hero teams up with the friendly neighborhood Spider-Man — but they're about to have their hands full with the attack of a 50-foot tall redheaded madwoman! Then, everyone loves Carol's adorable cat, Chewie — but is there more to this feisty feline than meets the eye? And just what is a Flerken anyway? In space, no one can hear you meow! And the modern-day Captain Marvel shares an adventure through time with someone she never thought she would see again — her fallen friend and inspiration, the Kree legend named Mar-Vell!